SOME DIFFICULTIES IN TRANSLATING SCIENTIFIC TEXTS - Trimadona, Eliza (Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri (IAIN) Kerinci, 2016)
SOME DIFFICULTIES IN TRANSLATING SCIENTIFIC TEXTS